A review of weldability of carbon steel in arc-based welding processes - Oluwasegun S. Odebiyi (Taylor & Francis Group, 2019)
The weldability of carbon steel is determined by carbon equivalent (CE) for predicting/estimating preheat temperatures necessary for weld integrity of the weldment. The microstructure of the welded carbon steel at the heat affected zone (HAZ) plays an essential role in the mechanical properties of the weldment, thus, painstakingly selecting welding process and parameters to slowdown the cooling rate are ensued by sound weld quality and crack free weld (enhanced service performance). This research work reviews the effects of various welding processes and parameters on microstructure and mechanical properties of carbon steels in arc-based welding.